Respiratory health and individual estimated exposure to traffic-related air pollutants in a cohort of young children. Issue 1 (15th August 2006) - Morgenstern, V; Zutavern, A; Cyrys, J; Brockow, I; Gehring, U; Koletzko, S; Bauer, C P; Reinhardt, D; Wichmann, H-E; Heinrich, J
Abstract : Objectives: To estimate long-term exposure to traffic-related air pollutants on an individual basis and to assess adverse health effects using a combination of air pollution measurement data, data from geographical information systems (GIS) and questionnaire data. Methods: 40 measurement sites in the city of Munich, Germany were selected at which to collect particulate matter with a 50% cut-off aerodynamic diameter of 2.5 µm (PM2.5 ) and to measure PM2.5 absorbance and nitrogen dioxide (NO2 ). A pool of GIS variables (information about street length, household and population density and land use) was collected for the Munich metropolitan area and was used in multiple linear regression models to predict traffic-related air pollutants. These models were also applied to the birth addresses of two birth cohorts (German Infant Nutritional Intervention Study (GINI) and Influence of Life-style factors on the development of the Immune System and Allergies in East and West Germany (LISA)) in the Munich metropolitan area. Associations between air pollution concentrations at birth address and 1-year and 2-year incidences of respiratory symptoms were analysed. Results: The following means for the estimated exposures to PM2.5, PM2.5 absorbance and NO2 were obtained: 12.8 μg/m 3, 1.7×10 −5 m −1 and 35.3 μg/m 3, respectively. Adjusted odds ratios (ORs) for wheezing, cough without infection, dry cough at night, bronchial asthma, bronchitis and respiratory infections indicated positive associations with traffic-related air pollutants. After controlling for individual confounders, significant associations were found between the pollutant PM2.5 and sneezing, runny/stuffed nose during the first year of life (OR 1.16, 95% confidence interval 1.01 to 1.34) Similar effects were observed for the second year of life. These findings are similar to those from our previous analysis that were restricted to a subcohort in Munich city. The extended study also showed significant effects for sneezing, running/stuffed nose. Additionally, significant associations were found between NO2 and dry cough at night (or bronchitis) during the first year of life. The variable "living close to major roads" (<50 m), which was not analysed for the previous inner city cohort with birth addresses in the city of Munich, turned out to increase the risk of wheezing and asthmatic/spastic/obstructive bronchitis. Conclusions: Effects on asthma and hay fever are subject to confirmation at older ages, when these outcomes can be more validly assessed.